A atuação repressiva do DOI/CODI/II Exército: a visão militar e a justiça de transição nas iniciativas cíveis do Ministério Público Federal - Souza, Diego Oliveira de (2015)
This dissertation is the result of research project, linked to the line of research Migrations and Work, of the Graduate Program in History at the Federal University of Santa Maria (UFSM), developed in its final period with research grant CAPES/DS. Its general objective is to synthesize the repressive actions of the DOI/CODI/II Army, at the time of the confrontation of political resistance of the Civil-Military Dictatorship, in particular between 1970 to 1977, through the military vision and contrast arising from use of the concept of transitional justice, in the quest for accountability and repair of systematic human rights abuses. Furthermore, as a result of the developments of State strategies aimed at the maintenance of national security, in that same time span, the DOI-CODI/II Army detained approximately 6,897 people, and have been identified officially, through the Presidency of the Republic, 64 cases of killings and forced disappearances by its functional apparatus. To achieve the objective proposed were elaborated the following issues: (a) In that location for the bases for legitimacy of the repressive structure of the DOI-CODI/II Army, in the panorama of the formation of the strategic thinking about national security policy, in the period preceding the years 1970-1977? (b) considering the cases of deaths and forced disappearance, the police-military apparatus of the DOI/CODI/II Army, exposed in the book right to memory and truth, official report of the Presidency of the Republic, to what extent the concept of transitional justice collaborates with the construction of historical knowledge about the repressive actions of the DOI-CODI/II Army? In this way, the first chapter of the dissertation is dedicated to the theme of military thought and its external and internal influences on demarcation of national security policy, which aims to carry out the search for legal/formal basis for the development of the repressive actions of the DOI-CODI/II Army. The itinerary of military thought between the Escola Superior de Guerra (ESG), the National Security Council and the National strategic concept points the way to better understand the repressive actions of the DOI-CODI/II Army. In this sense, the aim of this chapter is the military thinking about national security policy, which emphasizes the influence of the Escola Superior de Guerra (ESG) for the development of the military strategy of repressive activities in Brazilian society. The second chapter has as main theme the repressive policy adopted by the Civil-Military Dictatorship, developed by its military-police apparatus to eliminate political resistance. The military vision about the repressive actions of the DOI-CODI/II Army is concentrated mainly in this chapter, in particular, in public demonstrations that repressive body commanders writings. The third and final chapter of the dissertation deals with transitional justice measures, proposed by the MPF, to combat the impunity of human rights abuses committed in the course of the activities of the DOI/CODI/II Army. In this chapter, the study focuses the civil action, the MPF initiative in São Paulo, where notably public civil actions were examined related to the repressive actions of the DOI-CODI of Sao Paulo.